2005
DOI: 10.1143/jjap.44.l505
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Thick AlN Layer by Hydride Vapor Phase Epitaxy

Abstract: Thick AlN crystals were grown by conventional hydride vapor phase epitaxy (HVPE) on AlN/sapphire templates under low pressure (∼15 Torr) at high temperature (1100°C–1200°C). Colorless, mirror-like AlN films were obtained at the growth rates of up to 20.6 µm/h. The best root mean square (RMS) value of atomic force microscope (AFM) observations for the AlN surface was 2.34 nm. The typical values of full width half maximum (FWHM) of X-ray rocking curves for (0002) and (1012) diffraction of AlN films were 173–314 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…HVPE has produced thick AlN films with growth rate as fast as 200 µm/h. This is the fastest HVPE growth rate hitherto reported for AlN with qualities comparable to what has been reported by other groups [4][5][6]. However, the layers grown by MEMOCVD exhibit the best qualities ever reported.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…HVPE has produced thick AlN films with growth rate as fast as 200 µm/h. This is the fastest HVPE growth rate hitherto reported for AlN with qualities comparable to what has been reported by other groups [4][5][6]. However, the layers grown by MEMOCVD exhibit the best qualities ever reported.…”
Section: Discussionsupporting
confidence: 84%
“…Various groups have reported AlN growth by bulk and seeded methods [1,2], but large-area AlN substrates are not available yet. HVPE appears to be an attractive technique to fabricate AlN substrates as reported by a few groups [3,4,5]. HVPE is being successfully utilized to grow free-standing GaN substrates with growth rates as high as 200 µm/h [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the present authors recently reported that HVPE of AlN using AlCl 3 , which does not react with quartz, is possible by preferential generation of AlCl 3 at the source zone [7,8]. Exploiting this fact, other research groups have also investigated HVPE of AlN [9,10]. However, little has been revealed about the effects of growth conditions on AlN growth.…”
Section: Introductionmentioning
confidence: 88%
“…However, numbers of literatures of HVPE growth of AlN are limited [6][7][8][9][10][11][12] because the AlCl generated in the source zone reacts with quartz glass reactor. Recently, our group has reported HVPE of AlN using AlCl 3 as an aluminum source on the basis of thermodynamic analysis results [6,8,10].…”
mentioning
confidence: 99%